2017
DOI: 10.3390/healthcare5030045
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Ageing in People with Intellectual Disabilities from Managers’ Perspective: A Qualitative Study

Abstract: An increasing number of people with intellectual disability (ID) are reaching older ages today although they experience more health problems than the older population without ID. Leaders in intellectual disability services can greatly influence the conditions for a healthy ageing, and the aim of the present study was to explore healthy ageing in this group from the perspective of the leaders. Interviews with 20 leaders were subjected to qualitative content analysis. The findings gave rise to the overall theme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 27 publications
(34 reference statements)
2
27
0
Order By: Relevance
“…Leaders at group homes and day program services in Sweden have expressed a wish for ageing people with intellectual disabilities to have the opportunity to see a physician at least once a year [42]. This has been introduced in several countries, and others have reported the need for such visits [13,17,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaders at group homes and day program services in Sweden have expressed a wish for ageing people with intellectual disabilities to have the opportunity to see a physician at least once a year [42]. This has been introduced in several countries, and others have reported the need for such visits [13,17,43].…”
Section: Discussionmentioning
confidence: 99%
“…This has been introduced in several countries, and others have reported the need for such visits [13,17,43]. Johansson and colleagues [42] reported a lack of experience and competence among staff in detecting the need for assistive devices or increased care. Based on the time since the institutions were closed in Sweden and that the cohort in the present study comprises older people with DS it is reasonable to expect that the absolute majority lived in supported housing such as group homes during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…If people with ID fall during vital activity because they rarely take part in other activities, the LSS act may not be not working as intended. In a recent study, leaders of group homes and daily activity centres highlighted the issue of decreased activity after retirement, suggesting that potential explanations were reduced social networks and lack of staff (Johansson et al 2017). Further studies should investigate if LSS indeed provides enough support for people with ID to lead an active and safe life.…”
Section: Discussionmentioning
confidence: 99%
“…The current study is part of a project about ageing in people with ID. Another element of the study (an interview study with managers) has been prevously published (Johansson et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Another study, a systematic review of care for older people with ID, reported that the staff lacked knowledge and methods and needed training and support related to questions of ageing (Innes et al, 2012). A previous study with leaders (Johansson et al, 2017) showed that ageing is a neglected question in their management role. Consequently, further investigation is required to more clearly understand how staff members provide care and services for older people with ID and how they experience and reflect on ageing with ID.…”
Section: Introductionmentioning
confidence: 99%